The socio-economic contribution of non-timber forest product trade to households in four villages in Zomba and Machinga Districts, Malawi - Mahonya, Sophie Manchichi (Rhodes University, Faculty of Science, Department of Environmental Science, 2017)
The principal aim of this study was to assess the socio-economic contribution of nontimber forest product (NTFP) trade to households in Zomba and Machinga, southern Malawi. Quantitative and qualitative data were collected through several methods, including a household survey using questionnaire interviews, focus group discussions, key informant interviews with individual traders, direct observations, and literature review. The quantitative data were analysed statistically using SPPS version 16.0 while the qualitative data were analysed thematically. NTFP trade was the third important source of cash income for 15% of the households, although the level of use, buying and selling of NTFPs varied across the four study villages. All households in all the study villages used firewood (100%), and most used thatch grass (94%), bamboo (96%), wood for building (92%), largely as construction materials. However, the percentage of households buying NTFPs was lower, with the maximum percentage of households being 50%. The percent of households engaged in selling at least one NTFP was lower still at 39%. Substantial cash incomes were generated from firewood and edible orchids sales which provided up to a maximum of Mk180,000, equivalent to US$456, per year. Households joined the trade mostly for an alternative source of cash income due to poverty and to meet basic needs when other options were not available or feasible. Cash income generated from NTFP trade acted as a safety net and a coping strategy when other avenues supporting livelihoods were not accessible. The socio-economic benefits derived from NTFP trade were associated with the quantities collected, sold, market forces influenced by the law of demand and supply. The small amounts of cash income generated by most households were important as they supplemented household cash needs. There was a strong association between NTFP trade as one of the important sources of cash income and the number of months a household had food from their own garden in a year. There was a significant relationship though weak between ranking of NTFP trade and livestock ownership by households. Value chain analysis was used as an analytical tool to understand the processes involved in NTFP trade. The value chains for the products under study were short, dominated by traders and some intermediaries. Most of the products were sold in local markets with little value addition. This study recommends that policy makers should integrate NTFPs into their development plans, emphasizing the establishment of management strategies that will enhance availability and sustainability of the resource. NTFPs contributed to the livelihoods of the households socially and economically through provision of food, cash income, energy for cooking, medicine and construction materials.
Keywords: Uncatalogued